Diagnostic Performance of an Artificial Intelligence System in Breast Ultrasound - O'Connell, Avice M; Bartolotta, Tommaso V; Orlando, Alessia; Jung, Sin-Ho; Baek, Jihye; Parker, Kevin J (Journal of ultrasound in medicine, 2022)
We study the performance of an artificial intelligence (AI) program designed to assist radiologists in the diagnosis of breast cancer, relative to measures obtained from conventional readings by radiologists. A total of 10 radiologists read a curated, anonymized group of 299 breast ultrasound images that contained at least one suspicious lesion and for which a final diagnosis was independently determined. Separately, the AI program was initialized by a lead radiologist and the computed results compared against those of the radiologists. The AI program's diagnoses of breast lesions had concordance with the 10 radiologists' readings across a number of BI-RADS descriptors. The sensitivity, specificity, and accuracy of the AI program's diagnosis of benign versus malignant was above 0.8, in agreement with the highest performing radiologists and commensurate with recent studies. The trained AI program can contribute to accuracy of breast cancer diagnoses with ultrasound.